Aquifer as a groundwater object - Сердюк, О. В. (Theory and practice of jurisprudence, 2016)
In the article determinations of the legal concepts "aquifer" and "water object" are analyzed from the standpoint of a logical correctness, pithiness and correlation with natural-science definitions. Splitting up of the aquifers on the various classification bases is researched. Legislative fixing of classification of the aquifer on conditions of stratification and protection is offered.